2023
DOI: 10.1038/s41419-023-06078-3
|View full text |Cite
|
Sign up to set email alerts
|

The activated CD36-Src axis promotes lung adenocarcinoma cell proliferation and actin remodeling-involved metastasis in high-fat environment

Li-Zhong Liu,
Bowen Wang,
Rui Zhang
et al.

Abstract: Obesity/overweight and lipid metabolism disorders have become increased risk factors for lung cancer. Fatty acid translocase CD36 promotes cellular uptake of fatty acids. Whether and how CD36 facilitates lung adenocarcinoma (LUAD) growth in high-fat environment is unknown. Here, we demonstrated that palmitic acid (PA) or high-fat diet (HFD) promoted LUAD cell proliferation and metastasis in a CD36-dependent manner. Mechanistically, CD36 translocated from cytoplasm to cell membrane and interacted with Src kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 52 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…In previous studies, it has been demonstrated that CD36-mediated cancer is associated with AKT pathway activation, as observed in gastric cancer and hepatic carcinoma (Luo et al 2021 ; Pan et al 2019 ). It was shown that the Src/PI3K/AKT axis is involved in CD36-mediated HCC and lung cancer development (Liu et al 2023 ; Luo et al 2021 ). In this current study, we also indicated that the AKT-mTOR pathway was activated by FFAs or HFD, which was associated with the enhanced expression of CD36.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been demonstrated that CD36-mediated cancer is associated with AKT pathway activation, as observed in gastric cancer and hepatic carcinoma (Luo et al 2021 ; Pan et al 2019 ). It was shown that the Src/PI3K/AKT axis is involved in CD36-mediated HCC and lung cancer development (Liu et al 2023 ; Luo et al 2021 ). In this current study, we also indicated that the AKT-mTOR pathway was activated by FFAs or HFD, which was associated with the enhanced expression of CD36.…”
Section: Discussionmentioning
confidence: 99%